The effects of non performing loans on commercial banks in Zimbabwe: a case of BancABC - Manyika, Lovemore (Midlands State University, 2017)
The purpose of the research was to evaluate the effects of Non Performing Loans on commercial banks Zimbabwe examining a case of BancABC. A background of a continuously rising trend in the bank’s Non Performing Loans has been has been a major cause for concern an questions have been raised as to whether or not the causes are known. In order to achieve this objective the research reviewed and consulted literature from several authorities to access in-depth knowledge of the research subject. The research used a sample size of thirty two employees from BancABC and two bank managers, as well as making use of both primary and secondary sources of collecting data. The respondents whether or not the determinants of Non Performing Loans were known and also the strategies they best thought could curb on the Non Performing Loans. The research found that weak risk management had severely cost BancABC as this had been reflected by its Non Performing Loans. The research also looked at the various strategies that can be adopted to come out of the problem. The results showed that procedures and policies, despite being in place, are not being properly observed internally. The research recommends that there be formal meetings of the bank and the borrower so as to facilitate communication and bridge the gap between the two parties.